2015
DOI: 10.1093/schbul/sbv016
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effect of Early Interventions for Psychosis on the Usage of Inpatient Services

Abstract: Objectives:To review and synthesize the currently available research on whether early intervention for psychosis programs reduce the use of inpatient services.Methods:A systematic review was conducted using keywords searches on PubMed, Embase (Ovid), PsycINFO (ProQuest), Scopus, CINAHL (EBSCO), Social Work Abstracts (EBSCO), Social Science Citations Index (Web of Science), Sociological Abstracts (ProQuest), and Child Development & Adolescent Studies (EBSCO). To be included, studies had to be peer-reviewed publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 35 publications
0
34
0
3
Order By: Relevance
“…Comparison with earlier time periods in Ontario health administrative data suggests that differences could also be due to declining hospitalization rates over time — we previously observed that 38% of first‐episode cases were hospitalized at first diagnosis between 1999 and 2008 (Anderson & Kurdyak, ), compared to 10% in the current study. This difference may have resulted from decreases in the number of psychiatric hospital beds (Sealy & Whitehead, ) and an increase in the provision of early psychosis intervention services (Archie, Hobbs, & Menezes, ; Cheng, Dewa, & Goering, ) over this time period—both of which are related to decreasing hospitalization rates (Randall et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison with earlier time periods in Ontario health administrative data suggests that differences could also be due to declining hospitalization rates over time — we previously observed that 38% of first‐episode cases were hospitalized at first diagnosis between 1999 and 2008 (Anderson & Kurdyak, ), compared to 10% in the current study. This difference may have resulted from decreases in the number of psychiatric hospital beds (Sealy & Whitehead, ) and an increase in the provision of early psychosis intervention services (Archie, Hobbs, & Menezes, ; Cheng, Dewa, & Goering, ) over this time period—both of which are related to decreasing hospitalization rates (Randall et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Substance and alcohol use were identified through contact with services, therefore we misclassified people who use substances or alcohol but have not presented to services. We were unable to examine some factors previously shown to impact hospitalization risk, including symptom severity (Lee et al, 2016;Robinson et al, 2019;Sipos, Harrison, Gunnell, Amin, & Singh, 2001), behavioural/functional disturbance (Turner et al, 2013;Wade, Harrigan, Harris, Edwards, & McGorry, 2006), enrollment in early psychosis intervention services (Randall et al, 2015), and being in a stable relationship (Ajnakina et al, 2019).…”
Section: Limitationsmentioning
confidence: 99%
“…Several meta‐analyses have shown EIP to be effective in reducing costly outcomes such as hospitalization, bed‐days and relapse rate, and in improving school or work involvement, as compared with treatment as usual. A 2014 report published by Rethink Mental Illness suggested that EIP and community‐based interventions generate economic gains mainly by their effects on relapse, reduced need for expensive care, and wider recovery outcomes (e.g., employment, housing, and physical health).…”
Section: Current Economic Evidence and Key Events In Mental Health Carementioning
confidence: 99%
“…A related challenge is that apparent savings found in a research study might not prove “cashable” in the real world. Early intervention psychosis teams might shorten inpatient stays, but will not generate actual savings unless inpatient beds close or staff are shed. Effective support for carers might reduce their time inputs (to which an evaluation might attach costs) or stress levels, but might not release resources transferable to other uses.…”
Section: Challenges and Responsesmentioning
confidence: 99%
“…These centers were established to provide psychosocial support services for patients with severe mental illness such as bipolar disorder, schizophrenia, and unspecified schizophrenia spectrum and other psychotic disorder (USS&OPD). Treatment adherence, quality of life and social cognitive functions are impaired in schizophrenia and bipolar disorder (6,7). Therefore, an integrated and multidimensional approach should be used to reduce non-adherence to treatment and increase the quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%